Efecto de la pandemia por COVID-19 en la gravedad de los síntomas del trastorno obsesivo-compulsivo - Tello Coronel, Ubaldo Nikolai (2023)
The COVID-19 pandemic is causing serious mental health problems, due to the distress caused and the policies of isolation and promotion of hygienic habits, presenting an increase in psychiatric disorders such as OCD. The assessment of OCD symptoms faces great challenges, a widely used approach is to assess the severity of symptoms, being the most replicated the Yale-Brown Obsessive-Compulsive Scale. This study conducted a systematic review with the aim of determining whether COVID-19 pandemic increases the severity of obsessive- compulsive symptoms in patients with OCD. The systematic search was conducted in PubMed, Google Scholar, SCIELO, Science Direct, Scopus, and Google Scholar databases; 11 articles were selected that met the inclusion and exclusion criteria, of which 7 found a significant increase in the severity of OCD symptoms during the pandemic and 4 found that the severity of their symptoms remained the same or was less severe. In this review we demonstrate that pandemic COVID-19 increases the severity of obsessive-compulsive symptoms in most OCD patients.